Responsabilidade social das empresas e valores humanos: um estudo sobre a atitude dos gestores brasileiros - Almeida, Filipe Jorge Ribeiro de (2007)
In the last decades of the 21st century, Corporate Social Responsibility (CSR) has become one of the most widely debated issues in business management, concerning researchers, politicians, managers and society at large. With multilateral implications in economic and social life, CSR refers, essentially, to the discussion about the boundaries of business intervention in society and the ethical limits that should regulate that intervention. It questions the impact of business practices in social well-being, the role left for corporations and for the State in attending to community needs, and which are, at last, the responsibilities that tie enterprises to society. In this research, CSR is approached from the perspective of its ethical foundations, based on the moral reasoning of the business manager, as a key organizational leader with relevant decision power. Specifically, the research aims to understand how the personal human value system and the ethical orientation of managers influence their attitude towards CSR, considering this attitude as an indicator of managerial behavior that translates into corporate performance. Theoretically, CSR concept is discussed and presented as a set of social commitments, based on a strict interpretation of its meaning. As to human values, its philosophical roots are briefly analyzed and Schwartz modern motivational theory is addressed as main reference for studying the personal value system of managers in this research. Concerning ethics, based on classical theory from moral philosophy, references are seek in John Stuart Mill¿s utilitarianism, Immanuel Kant¿s deontological absolutism, John Rawls¿s theory of justice and the ethics of virtue inspired by Aristotle¿s moral thoughts. Based on an extended literature review, research hypothesis are proposed as part of a theoretical model of analysis named Individual Attitude Towards Social Responsibility Model. In order to test the theory¿s empirical validity, it was conducted a field study with 252 Brazilian managers, mainly from the metropolitan areas of São Paulo and Rio de Janeiro. Results show that managerial attitude aligned with CSR principles is favored by conservative personal values, protectors of stability and centered on collective will, and by an ethical orientation based on egalitarianism as postulated by distributive justice principles. However, results also show that the influence of values and personal ethics on managerial attitude towards CSR only occur in managers younger than 30 years old. Findings and their meanings are discussed, as well as summarized in the Axiological and Ethical Determinants of Managers¿ Social Commitment Model. Finally, methodological limitations are evaluated and clues for further research are suggested.